Isolation and identification of α-amylase producing soil microorganisms and partial characterization of α-Amylase enzyme - Tamanna, Shams Tahsin (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.